Haemodynamic phenotypes and survival in patients with systemic sclerosis: the impact of the new definition of pulmonary arterial hypertension. Issue 3 (9th December 2019) - Xanthouli, Panagiota; Jordan, Suzana; Milde, Nicklas; Marra, Alberto; Blank, Norbert; Egenlauf, Benjamin; Gorenflo, Matthias; Harutyunova, Satenik; Lorenz, Hanns-Martin; Nagel, Christian; Theobald, Vivienne; Lichtblau, Mona; et al.
Abstract : Background: In this study, we investigated the impact of the new haemodynamic definition of pulmonary arterial hypertension (PAH) as proposed by the 6th PH World Symposium on phenotypes and survival in patients with systemic sclerosis (SSc). Methods: In SSc patients who were prospectively and consecutively screened for PAH including right heart catheterisation in Heidelberg or Zurich, haemodynamic and clinical variables have been reassessed according to the new PAH definition. Patients have been followed for 3.7±3.7 (median 3.4) years; Kaplan-Meier survival analysis was performed. Patients with significant lung or left heart disease were excluded from comparative analyses. Results: The final dataset included 284 SSc patients, 146 patients (49.2%) had mean pulmonary arterial pressure (mPAP) ≤20 mm Hg, 19.3% had mPAP 21–24 mm Hg and 29.4% had mPAP ≥25 mm Hg. In the group of mildly elevated mPAP, only four patients (1.4% of the whole SSc cohort) had pulmonary vascular resistance (PVR) values ≥3 Wood Units (WU) and could be reclassified as manifest SSc-APAH. Twenty-eight (9.8%) patients with mPAP of 21–24 mm Hg and PVR ≥2 WU already presented with early pulmonary vascular disease with decreased 6 min walking distance (6MWD) (p<0.001), TAPSE (p=0.004) and pulmonary arterial compliance (p<0.001). A PVR ≥2 WU was associated with reduced long-term survival (p=0.002). PVR and 6MWD were independent prognostic predictors in multivariate analysis. Conclusion: The data of this study show that a PVR threshold ≥3 WU is too high to enable an early diagnosis of PAH. A PVR threshold ≥2 WU was already associated with pulmonary vascular disease, significantly reduced survival and would be more appropriate in SSc patients with mild PAH.